2007
DOI: 10.1128/aem.01281-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Phenotypic Analyses Suggest a Network between the Transcriptional Regulators HrcA and σBinListeria monocytogenes

Abstract: Listeria monocytogenes HrcA and CtsR negatively regulate class I and III stress response genes, respectively, while B positively regulates the transcription of class II stress response genes. To define the HrcA regulon and identify interactions between HrcA, CtsR, and B , we characterized newly generated L. monocytogenes ⌬hrcA, ⌬ctsR ⌬hrcA, and ⌬hrcA ⌬sigB strains, along with previously described ⌬sigB, ⌬ctsR, and ⌬ctsR ⌬sigB strains, using phenotypic assays (i.e., heat resistance, acid resistance, and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 51 publications
4
89
1
1
Order By: Relevance
“…For example, microarray data did not show effects of the sigB deletion on transcript levels for mogR, which encodes a transcriptional repressor of flagellar and motility genes (30). While hrcA, which encodes a negative regulator, is positively regulated by B , microarray experiments showed no evidence that HrcA regulates flagellar genes (37). Previous studies have shown that an L. monocytogenes ⌬degU strain as well as a ⌬mogR strain has attenuated virulence in mouse models of infection (30,44,71).…”
Section: Resultsmentioning
confidence: 91%
“…For example, microarray data did not show effects of the sigB deletion on transcript levels for mogR, which encodes a transcriptional repressor of flagellar and motility genes (30). While hrcA, which encodes a negative regulator, is positively regulated by B , microarray experiments showed no evidence that HrcA regulates flagellar genes (37). Previous studies have shown that an L. monocytogenes ⌬degU strain as well as a ⌬mogR strain has attenuated virulence in mouse models of infection (30,44,71).…”
Section: Resultsmentioning
confidence: 91%
“…The first cluster contains five immotile variants showing extreme HHP and heat resistance. Resistance to various stresses, as seen for most variants, might be explained by simultaneous activation through regulatory networks of the different stress mechanisms, as previously described for HrcA, CtsR, and B in L. monocytogenes (10,11). The second cluster contains two stressresistant variants with anaerobic growth and aerobic biofilm formation similar to the wild type (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a large number of genes were found to be negatively influenced by B , in particular genes encoding flagellar and ribosomal proteins. Intriguingly, many of the B -dependent effects observed in these studies appear to be indirect, i.e., through secondary gene regulatory systems, such as the stress-related transcriptional regulators HrcA and CtsR, the key virulence regulator PrfA, and the RNA chaperone Hfq (15,16).…”
mentioning
confidence: 99%